2015
DOI: 10.1111/1759-7714.12229
|View full text |Cite
|
Sign up to set email alerts
|

Does the response to induction chemotherapy impact the timing of thoracic radiotherapy for limited‐stage small‐cell lung cancer?

Abstract: BackgroundTo investigate whether the response to induction chemotherapy (IC) would impact the timing of thoracic radiotherapy (TRT) in limited-stage small-cell lung cancer (LS-SCLC).MethodsA total of 146 patients with LS-SCLC who had received two to six cycles of IC followed by TRT from January 2009 to December 2011 at our hospital were included in this study. Patients were divided into two groups based on the time TRT was administered: early TRT (administered after 2–3 cycles of chemotherapy) or late TRT (adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Patients in the TRT group were stratified by the number of induction chemotherapy cycles they received prior to TRT. According to the previous research [ 15 ], we defined ERT as receiving TRT before or at the third cycle of chemotherapy, LRT was receiving TRT after the third cycle of chemotherapy. Specifically, the ERT group (≤3 cycles, n = 65) and the LRT group (>3 cycles, n = 122).…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the TRT group were stratified by the number of induction chemotherapy cycles they received prior to TRT. According to the previous research [ 15 ], we defined ERT as receiving TRT before or at the third cycle of chemotherapy, LRT was receiving TRT after the third cycle of chemotherapy. Specifically, the ERT group (≤3 cycles, n = 65) and the LRT group (>3 cycles, n = 122).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 4,212 records were searched, and 40 records were screened to quality assessment. Among the 40 records, 3 records (40,49,50) were excluded for high risk of bias and 37 records, consisting of 15 phase III RCTs (4, 5, 13-25), 12 phase II (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), and 10 retrospective studies (39,(41)(42)(43)(44)(45)(46)(47)(48)51), were finally included for analysis (Supplementary Figure 1). Long-term survival data of three single-arm phase II studies (35)(36)(37) were updated in another report (52).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For LD-SCLC, existing data concerning the impact of start of radiation on OS remain inconclusive. The results of Wang et al 21 con ne superiority in OS and response of patients with complete or partial remission after two or three cycles of initial chemotherapy. Further studies have shown superiority of an early start of thoracic radiation over a late or very late start.…”
Section: Discussionmentioning
confidence: 93%